Interaction of Regional Population and Employment over Time: identifying short-run effects and equilibrium adjustment - Wouter Vermeulen; Jos Van Ommeren (European Regional Science Association (ERSA), 2004)
We investigate the interaction of regional population and employment in a simultaneous model. A focus on regional time series allows us to innovate in two ways on the ongoing causality debate in the literature. Firstly, a dynamic specification is proposed that generalizes the often assumed lagged adjustment process and enables to identify both short and long-term effects. We argue that the long-run relationship between population and employment should be interpreted as a labour market equilibrium. A second improvement on current empirical evidence is the use of region and time-specific fixed effects. Because by applying these panel data techniques, unobserved heterogeneity on the regional level and national trends are controlled for, the identification of regional population-employment interaction is substantially less troubled by an omitted variables problem. The model is estimated on almost three decades of annual data for regions in The Netherlands. This dataset is unique because it includes internal migration, so that we can disentangle net migration and exogenous natural population increase in order to model population adjustment more accurately. Reflecting the geographical structure of the country, which is characterised by overlapping urban areas, we allow for interregional commuting. Our main findings are that in The Netherlands, employment growth responds to deviations from regional labour market equilibria, but net internal migration is only slightly affected by regional employment in the short run. This implies that equilibrium on regional labour markets is restored through adjustment of employment instead of population. It also illustrates the additional insight into dynamic adjustment processes that can be gained from distinguishing both short and long-run effects, the importance of which is confirmed by rejection of the lagged adjustment process hypothesis for our data. Finally, the dominance of supply side factors in the employment equation casts doubt on appropriateness of traditional regional export base and multiplier models, which heavily rely on the assumption that local factor supply constraints are absent.
Keywords: 330